Private Universities Bring Competition and End to Monopoly - Naik, B. M. (Journal of Engineering Education Transformations, 2005)
Private universities, although new to India, exist in the US from hundreds of years. Almost half of the 3500 US universities are private. They are managed and maintained either by the church, industry, or philanthropic organizations.